Pengaruh Minat dan Pendidikan Kewirausahaan terhadap Motivasi Berwirausaha (Studi Kasus Mahasiswa Tingkat IV Fakultas Ekonomi Universitas Samudra T.A 2018/2019) - Syardiansah Syardiansah (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
This research was conducted to find out how the influence of entrepreneurial interest and education on entrepreneurial motivation by level IV students of the Faculty of Economics, University of Ocean. The research method was conducted by surveying and distributing questionnaires to IV level students of the Faculty of Economics, University of Samudra in 2018. Based on the Slovin formula the sample was taken as many as 60 respondents representing 150 level IV students of the Faculty of Economics, Samudra University in 2018 consisting of Management Study Program students 30 people, Development Economics 60 people and Accounting 60 people. Based on the results of the analysis, the multiple linear regression equation Y = 0.351 + 0.543X1 + 0.389X2 is obtained. From this equation can be translated that the constant of 0.351 shows the value of motivation for entrepreneurship if the interest in entrepreneurship and entrepreneurship education is worth zero (fixed) of 35.1%. The value of the independent test variable (interest in entrepreneurship) shows a significance value of 0,000 <0,05. The value of the independent test variable (entrepreneurship education) shows a significance value of 0.001 <0.05. Simultaneously it is shown that the value of F sig is 0,000, because the value of F sig is 0,000 <0,05, it can be stated that the interests and education of entrepreneurship simultaneously have a significant effect on motivation for entrepreneurship. The coefficient of determination (R2) of 0.611 or 61.1% means the variability of entrepreneurial motivation variables which can be explained by the variability of interest in entrepreneurship and entrepreneurship education by 61.1%, while the remaining 38.9%, explained by other variables not included in the model this regression.